Analysis of Conization Results in Patients undergoing Hysterectomy for Uterine Adenocarcinoma - Drumond, Denise Gasparetti; Leite, Isabel Cristina Gonçalves; Rodrigues, Vivian de Oliveira; Pannain, Gabriel Duque; Carvalho, Miralva Aurora Galvão; Amaral, Renata Guimarães Rabelo do (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To observe if the histopathological result of a conization performed after cervical adenocarcinoma in situ diagnosis is compatible with the histopathological analysis of a subsequent hysterectomy.Methods The present descriptive and observational research consisted of the analysis of the medical records of 42 patients who were diagnosed with in situ adenocarcinoma postconization. The analysis consisted of whether there was compatibility between the histopathological reports of conization and hysterectomy and if there was an association between adenocarcinoma in situ and another neoplasia (squamous disease). Interpretation of any immunohistochemistry reports obtained was also performed. In addition, clinical and epidemiological data were also analyzed.Results A total of 42 conizations were performed, 33 (79%) were cold knife conizations and 9 (21%) were loop electrosurgical excision procedures (LEEPs). Of the patients analyzed, 5 (10%) chose not to undergo subsequent hysterectomy to preserve fertility or were < 25 years old. Out of the 37 patients with adenocarcinoma in situ who underwent subsequent hysterectomy, 6 (16%) presented with residual disease. This finding proved incompatible with the finding of the conizations, which had ruled out invasive cancer.Conclusion The prevalence of adenocarcinoma in situ increased in the past years. There is still a large part of the medical literature that advocates the use of conservative treatment for this disease, even though it is common knowledge that it is a multifocal disease. However, the majority of studies advocate that hysterectomy should remain the preferred treatment for women who have already completed their reproductive purpose.
Keywords: conization; hysterectomy; adenocarcinoma in situ